Digital-Based Educational Strategies For Msmes In Border Areas To Implement A Green Economy - Yeremia Niaga Atlantika; Benedhikta Kikky Vuspitasari; Eligia Monixa Salfarini; Rison Rison (UNIVED Press, 2025)
This research aims to describe effective educational strategies for digital-based MSMEs (Micro, Small, and Medium Enterprises) to implement a green economy in the border areas. The methodology used is a qualitative-descriptive approach. Data sources were collected through interviews employing 8 informants from 4 clusters of SMEs in the border areas. Data analysis was conducted through the processes of reduction, presentation, and conclusion drawing. It reveals the issues faced by SMEs in enhancing their knowledge, perceptions, and behaviors towards the green economy. The summarized data is then validated through FGD (Focus Group Discussion) activities based on PBL (Problem-Based Learning) involving all the informants. This PBL-based FGD process yields educational strategies aimed at developing digital technology-based literacy for the implementation of a green economy by SMEs in border areas.